2017
DOI: 10.1007/978-94-024-1251-2_6
|View full text |Cite
|
Sign up to set email alerts
|

mHealth, Health, and Mobility: A Culture-Centered Interrogation

Abstract: In this chapter, we examine the interplays of the symbolic and the material in the constructions of mHealth. By attending to the key themes that play out in discourses of mHealth, we examine critically the ways in which power plays out in the structuring of mHealth solutions. The articulation of mHealth as instrumental to generating positive health outcomes in communities across Asia erases the contexts within which mobile technologies are constituted. mHealth interventions reproduce the logics of the state an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…82 However, none of these integrate the culturally and linguistically tailored approaches used in in-person studies that have been shown to work in stroke prevention among communities of color and those with limited English proficiency. [83][84][85] Several studies have shown that community health care workers, care navigators, and health educators are important allies in helping patients navigate the complex health care system. A multidisciplinary team including community health care workers, 75 pharmacists, and nurses 86 in the delivery of chronic disease care and cardiovascular health has led to significant improvements in health literacy, risk factor control, self-management behaviors, lifestyle habits, clinical outcomes, and a decrease in inappropriate health care utilization.…”
Section: Secondary Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…82 However, none of these integrate the culturally and linguistically tailored approaches used in in-person studies that have been shown to work in stroke prevention among communities of color and those with limited English proficiency. [83][84][85] Several studies have shown that community health care workers, care navigators, and health educators are important allies in helping patients navigate the complex health care system. A multidisciplinary team including community health care workers, 75 pharmacists, and nurses 86 in the delivery of chronic disease care and cardiovascular health has led to significant improvements in health literacy, risk factor control, self-management behaviors, lifestyle habits, clinical outcomes, and a decrease in inappropriate health care utilization.…”
Section: Secondary Preventionmentioning
confidence: 99%
“…82 However, none of these integrate the culturally and linguistically tailored approaches used in in-person studies that have been shown to work in stroke prevention among communities of color and those with limited English proficiency. 83–85…”
Section: Secondary Preventionmentioning
confidence: 99%
“…While Singapore is a technologically fluent country with adequate resources to implement health app initiatives, efforts must be made to tailor health apps towards local experiences, values, and culture to fully optimize app usage. 20 Given the high awareness and positive attitudes towards health apps in Singapore, 21 there is considerable potential to build upon through focused but flexible goal setting and localization of content.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is no ultrasound-guided breast biopsy-training program in Nigeria, despite the country having over 350 radiologists in-country (WHO, 2018). While Global Health advocates have called for the implementation of interventions to enhance breast cancer screening and early detection in LMIC (Pace & Katz, 2015), previous studies of mHealth interventions provide a cautionary tale of “top down” program designs that lack consultation and engagement from local clinicians and healthcare workers (Dutta et al, 2018). The objective of this study, therefore, was to engage Nigerian cancer clinicians to understand current practice, need, and interest in mHealth ultrasound-guided breast biopsy, to inform the development of a training program that is relevant to the local context.…”
Section: Introductionmentioning
confidence: 99%